Pembuatan Hand Sanitizer sebagai salah satu upaya pencegahan Covid-19 di Kota Pekanbaru, Indonesia - Arisman Adnan; Nurhayati Nurhayati; Maria Erna; Ari Sulistyo Rini; Ody Azis Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
In early 2020, the world was shocked by the outbreak of new pneumonia that started in Wuhan, Hubei Province which then spread rapidly to more than 190 countries and territories. This outbreak is named coronavirus disease 2019 (Covid-19) which is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). People are not aware that their hands are often contaminated with bacteria and viruses during their activities. One of the simplest ways and can be done to prevent this is to wash your hands using soap or antiseptic, hand sanitizer. Washing your hands can reduce the number of bacteria by up to 58%. The advantages of hand sanitizers can kill germs in a relatively fast time. The active ingredients of hand sanitizers are generally alcohol group compounds with a concentration of ± 60% to 80% and the phenol group (triclosan) so that they have a mechanism of action by denaturing and coagulating cell protein germs. Therefore, making hand sanitizers in simple stages can be done alone in community service activities. This service aims to find out how high public awareness is in dealing with the Covid-19 outbreak in everyday life. Evaluation of the service activities that will be carried out is to see how many people are aware of the importance of protecting themselves and the environment and maintaining distance in order to break the chain of spreading the virus.